2011
DOI: 10.1177/1099800411413259
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Music as Therapy on the Overall Well-Being of Elderly Patients on Maintenance Hemodialysis

Abstract: In this study, the authors explored the use of music during hemodialysis (HD) as a complementary therapy to improve overall well-being in elderly patients. The authors recruited a convenience sample of 88 patients on maintenance HD from a teaching hospital in northern Taiwan and randomly assigned them to either an experimental group (n = 44) or a control group (n = 44). In the first week, participants in the experimental group created their own music playlists. During the second week, these participants listen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 21 publications
1
42
0
4
Order By: Relevance
“…Lin et al. conducted a study wherein patients listened to music for each hemodialysis session; the authors concluded that listening to music during the sessions creates a positive effect …”
Section: Discussionmentioning
confidence: 99%
“…Lin et al. conducted a study wherein patients listened to music for each hemodialysis session; the authors concluded that listening to music during the sessions creates a positive effect …”
Section: Discussionmentioning
confidence: 99%
“…Six items are classified as physiological (2,3,7,10,11,20) and 23 items (1,4,5,6,8,9,12,13,14,15,16,17,18,19,21,22,23,24,25,26,27,28,29) are classified as psychosocial stressors in HSS. Scale is a 5-Likert-type scale (always: 5, mostly: 4, sometimes: 3, rarely: 2, never: 1).…”
Section: Hemodialysis Stressor Scale (Hss)mentioning
confidence: 99%
“…2 HD creates stress and anxiety for the patients. 3 Many HD patients, who have confronted with physical and psychological stressors, display psychological problems such as depression and anxiety. 4 Recently, dim environment, massage, and music treatment have been used to reduce stress.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Taiwan showed that listening to music during HD session enhances patients' adherence to therapy and improve their mood . In our study, the frequency of manipulative methods was 85.8%.…”
Section: Discussionmentioning
confidence: 46%